A Vygotskian-constructivist intervention program in reading for preservice teacher education students - Hermosura, Jose S. (2005)
The main purpose of this study was to enhance the academic performance of Second Year BEED students of Leyte Normal University through a reading intervention program that gave emphasis to learning and reading comprehension strategies using a variety of texts. As an experimental research, the investigation used the Solomon four-group design to analyze the data resulting from the experiment. The results showed that the reading intervention program was highly effective in changing the students' perception of college work as well as in improving their academic performance. It was recommended that intervention programs of this nature be limited to 10 comprehension strategies so that they would be internalized by all students attending the program.